THE PROXIMATE COMPOSITION IN FLOUR SEA CUCUMBER(Paracaudinaaustralis) - Munisatul Haq; Rahman Karnila; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractBerunok is a type of sea cucumber that is widely distributed in the waters of Karimun Regency, which is usually consumed raw by coastal Malay people and has not been used optimally. This study aims to determine the amount of proximate content in berunok flour (Paracaudinaaustralis). The proximate tests conducted are water, fat, protein, ash, and carbohydrates by difference. The results showed that the proximate content of P. australis flour included water content of 8.19% (bb), ash content 37.21% (bk), protein content of 48.78% (bk), fat content of 3.44% (bk). , as well as carbohydrate content by 10.57% difference.With an average yield value of 83.34%. Keywords:Proximate, Sea cucumber